2012
DOI: 10.1016/j.jiph.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of toxigenic Vibrio cholerae with new multiplex PCR

Abstract: This multiplex PCR method has higher sensitivity and specificity than other methods. The proposed test provides an appropriate and sensitive tool for detecting the presence of toxigenic and pathogenic V. cholerae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 16 publications
0
26
1
2
Order By: Relevance
“…They reported that this developed method is able to detect 8.5 -85 pg of genomic DNA and 10 -100 colony-forming units of V. Cholerea. In addition, the specificity of this technique is 100% (11). In our previous study, we developed a multiplex PCR to detect hlyA, ctxB and tcpI as virulence and regulatory genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that this developed method is able to detect 8.5 -85 pg of genomic DNA and 10 -100 colony-forming units of V. Cholerea. In addition, the specificity of this technique is 100% (11). In our previous study, we developed a multiplex PCR to detect hlyA, ctxB and tcpI as virulence and regulatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, trained and expert technicians are required to perform the detection processes correctly. Since these requirements are not available in some medical laboratories, eliminating these problems with a quick and simple method is desirable (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Up to present, polymerase chain reaction (PCR) is the most powerful analytical method of nucleic acid detection by virtue of its higher sensitivity and specificity . Multiplex PCR is a suitable method for early detection of pathogens .…”
Section: Introductionmentioning
confidence: 99%
“…5 Up to present, polymerase chain reaction (PCR) is the most powerful analytical method of nucleic acid detection by virtue of its higher sensitivity and specificity. [6][7][8] Multiplex PCR is a suitable method for early detection of pathogens. [9][10][11][12] However, owing to the mutual competition and interference between primers, the success rate of obtaining the target DNA varies.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a plethora of real-time PCR assays for the detection of V. cholerae have been published. Three examples are the assays published by Huang et al (2009), Koskela et al (2009) and Mehrabadi et al (2012) While the elaborate multiplex assays typically published in the literature are technologically impressive, almost none of these include a single process control which is carried through both nucleic acid extraction and PCR amplification steps. In addition, most target several virulence genes which may introduce unnecessary complexity when the principal concern is to detect toxigenic V. cholerae in the simplest way possible.…”
Section: Introductionmentioning
confidence: 99%